Exploring the Effect of Cash Bonuses on Employees’ Innovativeness and Creativity in the Nigerian Banking Sector (International Journal of Management and Sustainability, 2022)
Employees’ performance is a major concern of organizational leaders, especially those in the human resources department. This paper, therefore, examined the effect of cash bonuses on employees’ innovativeness and creativity in deposit money banks in Nigeria. A self-administered questionnaire was used to source data from a sample of 364 employees working in various categories of nine (9) selected deposit money banks in Lagos State, Nigeria. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test the hypothesis. The results indicated that cash bonuses have a significant effect on employees’ innovativeness and creativity in deposit money banks in Lagos State, Nigeria (β = 0.701, t = 27.902, p < 0.05). This finding implied that cash bonuses are an essential driver of employees’ innovativeness and creativity in the Nigerian banking industry. The study recommended that the management of deposit money banks in Nigeria manage their organizational reward system to ensure better employee performance. Finally, the study’s limitations include that the sample used in this study only involved nine deposit money banks in Lagos State. Future research should include other banks in the sector. Moreover, future studies should include additional reward system variables that were not included in the present study.